Djibouti : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2009)
Following a participatory process involving all development players, the Poverty Reduction Strategy Paper (PRSP) on Djibouti sets goals for poverty reduction and improvement of inhabitants' living conditions. Analysis of the results of the first three years of implementation of the PRSP reveals a number of significant achievements but shows that chronic weaknesses are still undermining the country's development efforts. These results were achieved through implementation of priority measures in the social sectors and in the areas of growth support and preservation of macroeconomic stability.